A Study on the Influence of Conformity Behaviors, Perceived Risks, and Customer Engagement on Group Buying Intention: A Case Study of Community E-Commerce Platforms - Ou, Chueh-Chu; Chen, Kuan-Liang; Tseng, Wei-Kuo; Lin, Ya-Yun (Sustainability, 2022)
This study mainly probed into the factors influencing consumers’ OGB intention on community e-commerce platforms, built models that included facets of conformity behaviors, perceived risks, customer engagement, and OGB intention, and focused on whether there is a mediating effect on customer engagement and an interference effect on perceived risks. The subjects of this study were consumers with OGB experience on community e-commerce platforms. The results show that conformity behaviors have a significant positive impact on customer engagement and OGB intention; thus, when customers have insufficient information or relevant knowledge of OGB, the comments or recommendations of their relatives and friends would influence their engagement and OGB intention. Moreover, this study found that customer engagement has a complete mediating effect, which indicates that conformity behaviors can influence OGB intention through customer engagement. In addition, this study found that perceived risks have an interference effect, meaning that when consumers sense high risks, the OGB intention is weakened through customer engagement. This shows that in the OGB organizations of the community e-commerce platforms, it is recommended that more attention be paid to customer engagement; it is also a topic worthy of discussion in practical business applications.